UI/UX EPT Website Improvement using Human-Centered Design and User Experience Questionnaire Methods - Kurnia Ramadhan Putra; Galang Setia Yudana (Computing and Education Technology Journal, 2026)
Website English Proficiency Test (EPT), which functions as a registration system for student English proficiency tests, still exhibits several UI and UX issues, including unclear navigation flow, inconsistent visual design, limited information accessibility, and inefficient interaction processes. These limitations negatively affect usability, user satisfaction, and the overall effectiveness of the system. This study aims to improve the User Interface (UI) and User Experience (UX) of the EPT website by applying the Human-Centered Design (HCD) approach combined with the User Experience Questionnaire (UEQ) as an evaluation tool. The study involved 100 respondents selected using purposive sampling, with data collected through interviews and UEQ questionnaires, and analyzed using mean comparison and UEQ benchmark analysis. The results show significant improvements across all UEQ dimensions, namely Attractiveness (0.64 to 1.60), Perspicuity (0.77 to 1.85), Efficiency (0.81 to 1.65), Dependability (0.86 to 1.75), Stimulation (0.43 to 1.75), and Novelty (0.16 to 1.65), with most dimensions falling into the Good to Excellent categories. These findings indicate that the redesigned interface significantly enhances usability, efficiency, and visual appeal. The novelty of this study lies in the integration of the HCD approach with UEQ-based evaluation using a before-and-after (as-is vs to-be) comparison framework. The implications of this study suggest that user-centered design approaches can be systematically applied to improve digital service quality, increase user satisfaction, and support more efficient academic service systems.